Winplot Application for the Development of Constructivism-Based Mathematics Learning at PGRI 24 High School Jakarta - Ek Ajeng Rahmi Pinahayu; Luh Putu Widya Adnyani; Risma Nurul Auliya (Institut Teknologi Nasional, Bandung, 2022)
Mathematics has many abstract concepts that are hard to understand by students. Learning media as an intermediary play an important role in interpreting difficult materials to them. One of the learning media used by teachers related to mathematics equations and functions is Winplot. This community service is implemented at SMA PGRI 24 Jakarta in 2018. The purposes of this activity are (1) assisting teachers to build learning materials based on constructivism, (2) Assisting teachers to create teaching materials that are interesting and easy to understand by students, and (3) Improving the quality of schools through learning media implementation in teaching-learning activities, such as Winplot. The training method consists of several stages as follows (1) observation and interview, (2) presentation and discussion, and (3) evaluation. The results show that (1) teachers can improve their teaching performances based on constructivism, (2) teachers can develop learning materials which is easy to understand as well as can create an interesting learning atmosphere, especially in subjects related to quadratic equations and functions, (3) the quality of learning and teaching activities in school increases.